2018
DOI: 10.1016/j.str.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Ripk4 Reveals Dimerization-Dependent Kinase Activity

Abstract: Receptor-interacting protein kinase 4 (RIPK4) is a highly conserved regulator of epidermal differentiation. Members of the RIPK family possess a common kinase domain as well as unique accessory domains that likely dictate subcellular localization and substrate preferences. Mutations in human RIPK4 manifest as Bartsocas-Papas syndrome (BPS), a genetic disorder characterized by severe craniofacial and limb abnormalities. We describe the structure of the murine Ripk4 (MmRipk4) kinase domain, in ATP- and inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
(43 reference statements)
1
15
0
2
Order By: Relevance
“…However, the interaction between RIPK4 and KRT14 was particularly mediated by RIPK4's N-terminal kinase domain ( Figure 1B). Previously, RIPK4's kinase activity was shown to be dispensable for RIPK4 interaction with IRF6 (Huang et al, 2018). Similar to this report, our result showed that RIPK4 kinase activity is not necessary for RIPK4/KRT14 interaction ( Figure 1C).…”
Section: Discussionsupporting
confidence: 90%
“…However, the interaction between RIPK4 and KRT14 was particularly mediated by RIPK4's N-terminal kinase domain ( Figure 1B). Previously, RIPK4's kinase activity was shown to be dispensable for RIPK4 interaction with IRF6 (Huang et al, 2018). Similar to this report, our result showed that RIPK4 kinase activity is not necessary for RIPK4/KRT14 interaction ( Figure 1C).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, Ser25 is also present in RIPK2 and in RIPK4 (Fig. 6a) and crystal structures of active RIPK2 53,54 and RIPK4 55 indicate that Ser25 helps to seal the nucleotide binding site near the ribose and α-phosphate of the bound nucleotide (Fig. 6c).…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic domain crystal structure (5WNI) of mouse RIPK4 from Protein Data Bank (PDB) was used to analyze the effect of Asp161His substitution (Huang et al, 2018). Since, the conserved Asp143 residue had been replaced with Asn in the 5WNI model, we converted this substitution to the wild type amino acid (Asp).…”
Section: Methodsmentioning
confidence: 99%